Representation and pluralism: an analysis of brazilian electoral thresholds throughout history (Revista Direito em Debate, 2022)
The paper discusses the institutional design adopted for the implementation of Electoral Thresholds throughout Brazilian history. The main objective is to explain the peculiarities of the model adopted in Brazil from the characteristics of the State in force at each time. Methodologically, we chose to review the literature, using the inductive method to make inferences. The work is justified due to the relevance that the theme has assumed since redemocratization, with the fight against party fragmentation occupying a prominent place on the legislative agenda. The conclusion of the work suggests that the Brazilian model of the Electoral Threshold would reflect characteristics of the State it self, with a clear migration from a repressive/authoritarian model to a model based on pluralism as a guiding principle.